Editorial: introduction to group research projects developed within an intensive programme in railway and logistics - Marin MARINOV (Transport Problems, 2014)
This paper introduces a special issue of the Journal Transport Problems on group research projects developed within the RailNewcastle summer school organised and held in Newcastle upon Tyne, North East England. The participants (both educators and students) worked together in multinational and multidisciplinary groups to produce research projects. The topics of the group research projects were based around railway and logistics-related problems. As a result a collection of the best articles is produced for the purposes of this special issue.